Construction of a carbon nanosphere aerogel with magnetic response for efficient oil/water separation. (28th October 2022) - Cui, Yan; Kang, Weiwei; Hu, Jifan
Abstract : A magnetic carbon nanosphere aerogel with high adsorption capacity was synthesized, which could realize positioning adsorption and rapid recovery. Abstract : Marine oil leakage and toxic chemical discharge accidents have occurred frequently, leading to serious water pollution problems. Thus, effective treatment of oily wastewater is imminent. Carbon aerogels are widely used for oil/water separation because of their unique structural properties. Herein, a carbon nanosphere aerogel (MCA) with abundant pores and magnetic response was synthesized using magnetic carbon nanospheres as precursors. The MCA demonstrates excellent adsorption properties for various oils and organic solvents (43.82–83.58 g −1 ) and good reusability. With good mechanical properties, the MCA could be recycled by simple extrusion. The adsorption capacity of the MCA was still 90.24% of the initial value after ten adsorption–compression cycles. In particular, importantly, the MCA could realize positioning adsorption and rapid recovery after adsorption saturation through a magnetic field. Large-scale oil in water could be separated and collected using a continuous oil/water separation device with the MCA as the filter. In short, the MCA is a promising adsorbent in oil spill treatment. This work has a good scientific research value and practical application prospect.